Enhancing students’ science outcomes through problem-based interactive flipbook e-module - Sindi Kharomah; Yayuk Mulyati; Muhammad Fajar Marsuki; Indra Fardhani; Erti Hamimi; Mochammad Hannats Hanafi Ichsan; Said Hasan; S. Sugiyanto (Universitas Muhammadiyah Malang, 2024)
The challenges of finding interesting and interactive teaching materials is one of the causes of low science learning outcomes. Accordingly, this study formulates valid, practical, and effective flipbook-based e-modules for improving junior high school students' science learning outcomes. The Research and Development (R&D) method with the ADDIE development model was adopted. Then, the effectiveness of proposed e-modules in improving cognitive learning outcomes through pretest and posttest questions was measured. The garnered data was analyzed using the t-test and N-Gain. The material aspect was declared valid with 87% accuracy, while the media aspect yielded 84% accuracy, falling under the valid category. The practicality test for the e-module conducted by involving the teacher resulted in a 97% score in the practical category. Similarly, the readability test conducted by involving the students resulted in a 93% score in the practical category. The analysis of the test results indicated a significant difference in cognitive learning outcomes before and after using flipbook-based e-modules, with a sig value of 0.000 < a = 0.05. The N-Gain test yielded a value of 0.70 in the medium criteria, placing the level of effectiveness in the moderately effective category. These results suggest that the implementation of the Problem-Based Learning (PBL) model, facilitated by flipbook-based interactive e-modules in learning activities, can enhance the science learning outcomes of junior high school students.